Escaping the rigidity trap: the functional spectrum of Tibetan formulas - Schwabl, Herbert (Frontiers in Human Dynamics, 2025)
Rigid pharmacopoeial regulations constrain traditional medicine, often excluding herbs due to strict compliance. Climate change and rising global demand threaten natural resources, while slow regulatory adaptation further restricts herbal ingredients. Narrow regulatory specificity and fragile resources create a rigidity trap, where regulations fail to accommodate the dynamic nature of traditional medicine. Traditional medical systems, such as Tibetan medicine, exhibit flexibility and resilience by utilizing diverse plant species for similar therapeutic effects—the functional spectrum of a formula. Rather than adhering to rigid pharmacopoeias, monographs should reflect the full functional spectrum of herbal materials historically and empirically used. Expanding pharmacopoeial monographs to reflect functional diversity preserves traditional formulas, safeguards medical knowledge, and enhances adaptability to modern challenges.